2014
DOI: 10.1128/aac.02574-13
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Activity, and Inhibition of the Carboxyltransferase β-Subunit of Acetyl Coenzyme A Carboxylase (AccD6) from Mycobacterium tuberculosis

Abstract: In Mycobacterium tuberculosis, the carboxylation of acetyl coenzyme A (acetyl-CoA) to produce malonyl-CoA, a building block in long-chain fatty acid biosynthesis, is catalyzed by two enzymes working sequentially: a biotin carboxylase (AccA) and a carboxyltransferase (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The conserved primary sequence and structure near the active site makes this enzyme attractive for developing new antibiotics. A few other compounds do inhibit bacterial ACCs (36)(37)(38)(39)(40), but the structure of thailandamide is different from those inhibitors. Further analysis of AccA and thailandamide may identify a path to a clinically useful drug.…”
Section: Discussionmentioning
confidence: 99%
“…The conserved primary sequence and structure near the active site makes this enzyme attractive for developing new antibiotics. A few other compounds do inhibit bacterial ACCs (36)(37)(38)(39)(40), but the structure of thailandamide is different from those inhibitors. Further analysis of AccA and thailandamide may identify a path to a clinically useful drug.…”
Section: Discussionmentioning
confidence: 99%
“…Acetyl-CoA carboxylase is comprised of two enzymes, biotin carboxylase and carboxyltransferase, and catalyzes the first committed step in fatty acid synthesis (167). Acetyl-CoA carboxylase is an antimicrobial target in M. tuberculosis (168), E. coli (169,170), other bacteria and most living organisms (reviewed by (171)). All of the chokepoints in Table 3 are essential genes in B. pseudomallei MSHR668 and K96243, as determined by blasting the chokepoint enzyme sequences against essential gene sequences in the Database of Essential Genes (172) and by comparing to the list of essential genes previously identified in K96243 (173).…”
Section: Discussionmentioning
confidence: 99%
“…Unit cell dimensions suggested that the crystals were unlikely to contain the entire AccA3:AccD6 complex, and the unit cell dimensions did not correspond to the previously solved AccD6 structures 24. Molecular replacement was performed using balbes 27 with AccA3 as the template sequence, and a structural solution was identified with a homodimer of AccA3 in the asymmetric unit, and no evidence of the AccD6 subunit.…”
Section: Methodsmentioning
confidence: 93%
“…While structures have been determined for three of the MTb AccD proteins, AccD1 (PDB:4Q0G), AccD5 [22], and AccD6 [24], there is no structure available for any of the AccA proteins. Here, we present the 1.94 A structure of a full-length construct of MTb AccA3.…”
Section: Databasementioning
confidence: 99%